Does capitalism disfavor women? Evidence from life satisfaction - Niclas Berggren; Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2023)
There is widespread concern, especially in certain feminist circles, that a market-oriented economic system, or capitalism, disfavors women. This could take many forms, such as lower wages for the same type of work, reduced career opportunities, disparities in ownership and the upholding of traditional gender roles. In all, this could influence overall life satisfaction such that capitalism confers more life satisfaction on men than on women. We test empirically whether this concern is justified. Using the epidemiological approach to rule out reverse causality, we first confirm previous findings that most areas of economic freedom (legal quality in particular, but also monetary stability, openness and regulation) are beneficial for general life satisfaction. When looking at women and men separately, we find virtually no statistically significant differences, and in the cases we do, the estimates reveal a more beneficial outcome for women. Hence, we conclude that capitalism does not seem to favor men more than women in terms of life satisfaction.
Keywords: B52; D02; D63; F13; H11; I31; K20; K38; P16; 330; Economic freedom; Capitalism; Market economy; Life satisfaction; Gender; Happiness